The antipsychotic drug lurasidone inhibits coronaviruses by affecting multiple targets - Baroni, Sara; Carletti, Tea; Donalisio, Manuela; Arduino, Irene; Cazzaniga, Irene; Giorgino, Toni; Esposito, Francesca; Porta, Alessia; Diomede, Luisa; De Luigi, Ada; Gobbi, Marco; Lembo, David; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Coronaviruses (CoVs) share key genomic elements critical for viral replication, suggesting the feasibility of developing therapeutics with efficacy across different viruses. In a previous work, we demonstrated the antiviral activity of the antipsychotic drug lurasidone against both SARS-CoV-2 and HCoV-OC43. In this study, our investigations on the mechanism of action of lurasidone suggested that the drug exhibits antiviral activity by targeting the papain-like protease (PL-Pro) of both viruses, and the Spike protein of SARS-CoV-2, thereby hampering both the entry and the viral replication. In vitro assays demonstrate that lurasidone significantly reduces viral load in infected cells, showing that the drug is a promising candidate for further development as a dual-action antiviral, offering a potential new strategy in the fight against COVID-19 and other coronavirus-related diseases.